Estimation of high-order aberrations and anisotropic magnification from cryo-EM data sets in RELION -3.1 - Zivanov, Jasenko; Nakane, Takanori; Scheres, Sjors H. W. (IUCrJ, 2020)
Methods are presented that detect three types of aberrations in single-particle cryo-EM data sets: symmetrical and antisymmetrical optical aberrations and magnification anisotropy. Because these methods only depend on the availability of a preliminary 3D reconstruction from the data, they can be used to correct for these aberrations for any given cryo-EM data set, a posteriori . Using five publicly available data sets, it is shown that considering these aberrations improves the resolution of the 3D reconstruction when these effects are present. The methods are implemented in version 3.1 of the open-source software package RELION .